Assessment of the Impact of Regional Characteristics and the Development of Event Tourism on Business Tourism in the Republic of Kazakhstan Based on Clusterization and a Regression Model - TRUSHEVA, Sharafat; ABDRAMANOVA, Gulzhan; ZHAKUPOV, Altynbek; YESSILOV, Assylkhan; BAYANDIN, Marat Asylbekovich (Journal of Environmental Management and Tourism; Vol 13 No 4 (2022): JEMT, Volume XIII, Issue 4(60), Summer 2022DO - 10.14505/jemt.v13.4(60).07, 2022)
Interest in the problem under study is determined, first, by the fact that business tourism is one of the most profitable and diversified types of tourism. Second, business tourism often performs a stimulating function for other sectors of the national economy. The paper demonstrates the significance of business tourism in the contemporary tourism industry and provides an analysis of research studies on business tourism, including those investigating prospects for the development of this sector in Kazakhstan. The study assesses the development of business tourism in 17 regions of Kazakhstan on the following indicators: event infrastructure, programs to promote the region as an event destination, regional policy in the event industry and activities of specialized coordinating bodies, experience in hosting major international events in the region, the tourism potential of the region. The findings suggest that the state and development prospects of business tourism vary in different regions of the Republic of Kazakhstan. The regions demonstrating a low level of development of business tourism require specialized measures for the improvement of the event infrastructure, implementation of programs for the promotion of the region as an event destination, and improvement of the state policy and activities of specialized coordinating bodies in the event industry.